2018
DOI: 10.4103/ijccm.ijccm_403_18
|View full text |Cite
|
Sign up to set email alerts
|

Turnaround time for red blood cell transfusion in the hospitalized patient: A single-center “Blood Ordering, Requisitioning, Blood Bank, Issue (of Blood), and Transfusion Delay” study

Abstract: Background and Aim:The turnaround time (TAT) for blood transfusion (BT) is an important quality indicator for the health-care institutions undertaking this procedure. There is no established national or international benchmark for this TAT due to the dearth of a published literature. We thus studied the TAT and the contributory procedures leading to delay in commencing a red blood cell transfusion in the hospitalized patient.Materials and Methods:Delay was captured for the blood order transcription, requisitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…According to a study that analysed the test sample processing time of ER patients, the sample processing time from the sample order to the laboratory reception was ~40 min 16 . Another study reported 47 min for the sample processing time in ER 17 . It took ~40 min from the ER order to the sample reception, 16 whereas in our study, this time was 16.00 min during the day, and 19.83 min at night.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…According to a study that analysed the test sample processing time of ER patients, the sample processing time from the sample order to the laboratory reception was ~40 min 16 . Another study reported 47 min for the sample processing time in ER 17 . It took ~40 min from the ER order to the sample reception, 16 whereas in our study, this time was 16.00 min during the day, and 19.83 min at night.…”
Section: Discussioncontrasting
confidence: 50%
“…16 Another study reported 47 min for the sample processing time in ER. 17 It took ~40 min from the ER order to the sample reception, 16 whereas in our study, this time was 16.00 min during the day, and 19.83 min at night. Despite its effectiveness in preventing WBIT, the sample processing time with utilising the new workflow did not increase compared to the time that without utilising the new workflow.…”
Section: Discussionmentioning
confidence: 53%
“…The response time from the request chain to the transfusion was studied in an Indian tertiary hospital, where the median time between the request and its arrival at the blood bank was 47 min, the bag preparation time was 55 min, and the total time to transfusion was 135 min 22 . The authors considered this interval excessively long, mainly due to the delay in sending samples to the blood bank (34 min), shortages and messengers who completed the task, and the physical distance between sectors.…”
Section: Discussionmentioning
confidence: 99%
“…Capacity building through training improves theatre efficiency and its output [12,14]. Surgical factors shown to increase TAT include complexity of surgeries leading to mental fatigue [15,16], ASA physical status [17], poor patient preparation [18,19] and unavailability of blood during surgery [20][21][22].…”
Section: Bivariate Associations Test On Factors Affecting Tatmentioning
confidence: 99%